2019
DOI: 10.3390/s19235138
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Evolution of Silica-Based Chromo-Fluorogenic Nanosensors

Abstract: This review includes examples of silica-based, chromo-fluorogenic nanosensors with the aim of illustrating the evolution of the discipline in recent decades through relevant research developed in our group. Examples have been grouped according to the sensing strategies. A clear evolution from simply functionalized materials to new protocols involving molecular gates and the use of highly selective biomolecules such as antibodies and oligonucleotides is reported. Some final examples related to the evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Thus, the system remains capped until the presence of the complementary oligonucleotide promoted the hybridization reaction and a displacement of the cap, resulting in pore opening and dye delivery (Figure 5). Based on these examples, different capped mesoporous silica materials for the selective detection of cations, anions, and biomolecules have been described by Martínez-Mañez in a recent review [93]. On the other hand, Martínez-Mañez et al reported a pioneering work related to the development of polyamine surface-functionalized mesoporous materials for anion recognition and signaling systems by dye delivery ([Ru(bipy) 3 ] 2+ ) as a function of pH in aqueous solution.…”
Section: Grafted Polyamine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the system remains capped until the presence of the complementary oligonucleotide promoted the hybridization reaction and a displacement of the cap, resulting in pore opening and dye delivery (Figure 5). Based on these examples, different capped mesoporous silica materials for the selective detection of cations, anions, and biomolecules have been described by Martínez-Mañez in a recent review [93]. On the other hand, Martínez-Mañez et al reported a pioneering work related to the development of polyamine surface-functionalized mesoporous materials for anion recognition and signaling systems by dye delivery ([Ru(bipy) 3 ] 2+ ) as a function of pH in aqueous solution.…”
Section: Grafted Polyamine Derivativesmentioning
confidence: 99%
“…Thus, the system remains capped until the presence of the complementary oligonucleotide promoted the hybridization reaction and a displacement of the cap, resulting in pore opening and dye delivery (Figure 5). Based on these examples, different capped mesoporous silica materials for the selective detection of cations, anions, and biomolecules have been described by Martínez-Mañez in a recent review [93]. Recently, Oshchepkov et al expanded the work of Kataev to prepare cryopolymers based on a naphthalimide fluorescent ligand that had shown selectivity toward phosphonate (66, Scheme 39).…”
Section: Grafted Polyamine Derivativesmentioning
confidence: 99%
“…However, in the last years the scope of this technology has been expanded toward applications in a variety of sectors such as agriculture [3,4], photovoltaic cells [5] external coatings [6] or personal care and cosmetics [7], employing as nanoparticles drug carriers (NPs) of organic [8][9][10] or inorganic [11] nature. Among these materials, microporous and mesoporous materials, due to their chemical inertness, homogeneous porosity and large internal surface area, have attracted considerable research interest for applications on the fields of drug delivery [12][13][14], catalysis [15][16][17], filtration and separation [18,19], gas adsorption [20,21] and storage [22,23], enzyme immobilisation [24,25], biomedical tissue regeneration [26,27], environmental remediation [28][29][30], chemical/biochemical sensing [31][32][33] and theranostics [34,35] mostly as nano-or microparticles, but also in core/shell formats or in combination with other properties such as magnetic ones [36,37]. Whereas typical microporous materials are crystalline framework solids, such as zeolites [38] with pore dimensions between 10-14 Å [39,40], mesoporous silica materials of the MCM-41 type, discovered in 1992 by researchers of the Mobil Research and Development Corporation ...…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Specifically, nanomaterials have resulted crucial for the development of some of such biosensors providing fast and accurate responses. [9] On that regard, the design of new hybrid bioorganic-inorganic materials allows to combine in a single entity the potential of nanomaterials with the recognition, selectivity and sensitivity properties of biomolecules. [10] Among nanomaterials utilized for the design of sensors, nanoporous anodic alumina (NAA) has become a suitable support due to its extraordinary features such as biocompatibility, the possibility to easily tune their surface and high loading capacity.…”
Section: Introductionmentioning
confidence: 99%